Myeloid heme oxygenase-1 promotes metastatic tumor colonization in mice - Lin, Heng-Huei (Cancer Sci, 2015)
Heme oxygenase-1 (HO-1) is a heme degradation enzyme with antioxidant and immune-modulatory functions. HO-1 promotes tumorigenesis by enhancing tumor cell proliferation and invasion. Whether HO-1 has an effect on cancer progression through stromal compartments is less clear. Here we show that the growth of tumor engrafted subcutaneously in syngeneic mice was not affected by host HO-1 expression. However, lung metastasis arisen from subcutaneous tumor or circulating tumor cells was significantly reduced in HO-1(+/−) mice comparing to wild type (WT) mice. The reduced lung metastasis was also observed in B6 mice bearing HO-1(+/−) bone marrow as comparing to WT chimeras, indicating that HO-1 expression in hematopoietic cells impacts tumor colonization at the metastatic site. Further experiments demonstrated that the numbers of myeloid cells recruited to pulmonary premetastatic niches and metastatic loci were significantly lower in HO-1(+/−) mice than in WT mice. Likewise, the extents of tumor cell extravasation and colonization at the metastatic loci in the early phase of metastasis were significantly lower in HO-1(+/−) mice. Mechanistic studies revealed that HO-1 impacted chemoattractant-induced myeloid cell migration by modulating p38 kinase signaling. Moreover, myeloid HO-1-induced expressions of vascular endothelial growth factor and interleukin-10 promoted tumor cell transendothelial migration and STAT3 activation in vitro. These data support a pathological role of myeloid HO-1 in metastasis and suggest a possibility of targeting myeloid HO-1 for cancer treatment.